Legal Consequences Of Self-Promotion By Notaries Through Social Media - Yustisya Zaharon; Fendi Setyawan; Fanny Tanuwijaya (Universitas Islam Darul Ulum, 2025)
Social media is one example of the many uses of technology due to the current of globalization. One profession that uses social media is the profession of notary to promote themselves. The form of self-promotion by Notaries through social media is a violation of Article 4 paragraph (3) of the Notary Code of Ethics, that Notaries are prohibited from publishing or promoting themselves, either alone or together by including their name and position, using print and/or electronic media, in the form of advertisements, congratulations, thanks, marketing activities, sponsorship activities, whether in the social, religious, or sports fields. The purpose of this study is to determine the results of legal self-promotion by notaries through social media. The research method used is normative juridical with a regulatory-statute approach and a conseptual approach. The results of the study revealed that the legal consequences for notaries who promote themselves through social media are only regulated in Article 6 paragraph (1) and (2) of the Notary Code of Ethics, the legal consequences of paragraph (1) include: Reprimand, Warning, Schorsing (temporary dismissal) from the Association, Onzetting (dismissal) from the Association, and Dishonorable Dismissal from the Association. Then, paragraph (2) states that sanctions imposed on members who violate the Code of Ethics are adjusted according to the quantity and quality of the violations committed. In conclusion, self-promotion by Notaries through social media is only regulated in Article 4 paragraph (3) of the Notary Code of Ethics. There is still ambiguity in Article 17 paragraph (1) letter i of the Notary Law, which only stipulates that Notaries are prohibited from engaging in other work that conflicts with religious norms, morality, or propriety that could affect the honor and dignity of the Notary position. However, it does not further regulate what work falls within the qualifications to affect the honor and dignity of the Notary position. This certainly creates legal uncertainty for Notaries.